2022
DOI: 10.2169/internalmedicine.9124-21
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Infarction in Patients with Philadelphia-negative Myeloproliferative Neoplasms

Abstract: Objective We retrospectively analyzed the prevalence and clinical features of splenic infarctions in patients with Philadelphia chromosome-negative myeloproliferative neoplasms (Ph -MPNs). Patients Patients diagnosed with essential thrombocythemia (ET), polycythemia vera (PV), prefibrotic/early primary myelofibrosis (pre-PMF), or PMF from January 1996 to October 2020 in Chungnam National University Hospital, Daejeon, Korea, were reviewed. Results A total of 347 patients (143 ET, 129 PV, 44 pre-PMF, and 31 PMF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Abdominal CT is not routinely performed during the initial evaluation of ET patients [ 32 ]. The clinical relevance of volumetric splenomegaly and splenic infarction detected using abdominal CT performed at the time of diagnosis of Ph - MPN has been previously evaluated [ 23 , 33 , 34 ]. Furthermore, in a small proportion of patients, abdominal CT has been used to detected asymptomatic malignancies at the time of diagnosis of Ph - MPN.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal CT is not routinely performed during the initial evaluation of ET patients [ 32 ]. The clinical relevance of volumetric splenomegaly and splenic infarction detected using abdominal CT performed at the time of diagnosis of Ph - MPN has been previously evaluated [ 23 , 33 , 34 ]. Furthermore, in a small proportion of patients, abdominal CT has been used to detected asymptomatic malignancies at the time of diagnosis of Ph - MPN.…”
Section: Discussionmentioning
confidence: 99%
“…PV patients with volumetric splenomegaly at diagnosis had a poorer prognosis than those without; however, the prognosis is better than that of patients with palpable splenomegaly [ 8 ]. In addition, abdominal CT performed at the time of MPN diagnosis revealed asymptomatic splenic infarction [ 9 ] and abdominal aortic calcification, indicative of a poor prognosis (submitted for publication). Several cancers are more common in Ph - MPN patients than in the general population [ 2 , 10 ].…”
mentioning
confidence: 99%
“…Despite these limitations, we found that a small population of Ph - MPN patients had asymptomatic splanchnic thrombosis and malignant tumors at the time of MPN diagnosis. As mentioned earlier, we previously reported that volumetric splenomegaly and asymptomatic splenic infarction detected by abdominal CT performed at the time of diagnosis are clinically useful for determining the diagnosis and prognosis [ 7 - 9 ]. The advantages of performing abdominal CT may offset the risks associated with radiation exposure and medical costs.…”
mentioning
confidence: 99%